A Lipschitz Stability Estimate for the Inverse Source Problem and the Numerical Scheme - Xianzheng Jia (Advances in Mathematical Physics)
We consider the inverse source problem for heat equation, where the source term has the form f(t)ϕ(x). We give a numerical algorithm to compute unknown source term f(t). Also, we give a stability estimate in the case that f(t) is a piecewise constant function.